Co-Expression Network Analysis Revealed That the ATP5G1 Gene Is Associated With Major Depressive Disorder - Zeng, Duan; He, Shen; Ma, Changlin; Wen, Yi; Xie, Ying; Zhao, Nan; Sun, Xirong; Wang, Dongxiang; Shen, Yifeng; Yu, Yimin; Li, Huafang (Frontiers in Genetics, 2019)
Major depressive disorder (MDD) is a leading cause of disability worldwide, although its etiology and mechanism remain unknown. The aim of our study was to identify hub genes associated with MDD and to illustrate the underlying mechanisms. A weighted gene co-expression network analysis (WGCNA) was performed to identify significant gene modules and hub genes associated with MDD in peripheral blood mononuclear cells (PBMCs) (n = 45). In the blue module (R2 = 0.95), five common hub genes in both co-expression network and protein–protein interaction (PPI) network were regarded as “real” hub genes. In another independent dataset, GSE52790, four genes were still significantly down-regulated in PBMCs from MDD patients compared with the levels in controls. Furthermore, these four genes were validated by quantitative real-time polymerase chain reaction (qRT-PCR) in PBMCs from 33 MDD patients and 41 healthy controls. The qRT-PCR analysis showed that ATP synthase membrane subunit c locus 1 (ATP5G1) was significantly down-regulated in samples from MDD patients compared with that in control samples (t= -2.89, p-value = 0.005). Moreover, this gene was significantly differentially expressed between patients and controls in the prefrontal cortex (z = -2.83, p-value = 0.005). Highly significant differentially methylated positions were identified in the Brodmann Area 25 (BA25), with probes in the ATP5G1 gene being significantly associated with MDD: cg25495775 (t = 2.82, p-value = 0.008), cg25856120 (t = -2.23, p-value = 0.033), and cg23708347 (t = -2.24, p-value = 0.032). These findings indicate that the ATP5G1 gene is associated with the pathogenesis of MDD and that it could serve as a peripheral biomarker for MDD.